SIFAT KIMIA TANAH AREA PASCA TAMBANG EMAS: (STUDI KASUS PERTAMBANGAN EMAS TANPA IZIN DI KENEGERIAN KARI KECAMATAN KUANTAN TENGAH, KABUPATEN KUANTAN SINGINGI) - Ervina Aryanti; Novita Hera (Jurnal Agroteknologi, 2019)
Gold mining activities cause damage the soil. This study aims to know soil chemical properties in post gold mining area (natural forest site, Cyperus kinglia site, open sedoment site and tailing site) after seven years. This research has been conducted from July to December 2017 in Kenegerian Kari gold mining area and central plantation laboratory. The research method used was quantitative descriptive with parameter of observation: pH, kation exchange, N, P, K, C-Organic and C/N ratio. The result showed that N, P, Phosphorus K, KTK content in the low and very low category. KTK, N, P, Phosphorus and K are categorized as low and very low. As well, the organic C content is low except in natural forests. While the C / N ratio category is high for all areas.